Literary warrant for Mindanao languages - Merced Jr., Briccio M. (PLAICongress, 2014)
Language is the fundamental of discourse in communication among people and culture. With its multi-ethnic composition, Mindanao languages have a variety of dialects and subgroups, construction and reconstruction of its protolanguage ancestral to Philippine languages and Southwest Sabah languages, which is the origin of most dialects of the Philippine-South Region (Lobel, 2003). These languages have difficulty entering information systems due to their unique characteristics and spelling variants. Literary warrant is in response to the content of the materials requiring categorization, and a body of literature must exist on a topic for a new class to be added (Reitz, 2014). This paper aims to deliver and present a structured order in a descriptive catalog and classification for Mindanao languages for easy retrieval and order using notations from LCSH, LCCS, Sears, DDCS, SIL, ethno-linguistic resources, and other existing systems. Different sources of information and references from books, Internet and database from library catalogs in Mindanao and other sources were utilized for this research.